Synthesis of Li1-xNi1+xO2 using malonic acid as a chelating agent - Thongtem T. (2014)
Li1-xNi1+xO2 powder was synthesized by polymerised complex method using malonic acid as a chelating agent. The carboxylate precursor was calcined in the temperature range 650-800°C for 14-48 h. The TG curves of malonic acid, lithium acetate dihydrate, nickel acetate tetrahydrate and the precursor were studied at 29.52-600°C. The FTIR spectra of the precursor without and with 650-800°C calcination were used to explain the vibrational bonding. At 750°C and above, only Li 1-xNi1+xO2phase was detected. The maximum [I(003/I(104)] and minimum [I(006+102)/I (101)] intensity ratios of the XRD spectra were used to determine the optimum temperature and time of calcination for preparation of Li 1-xNi1+xO2 powder. In addition, formation mechanism of Li1-xNi1+xO2 is proposed. The content of nickel, lithium, Ni3+/(Ni3+ + Ni2+) and mean oxidation state of nickel at 650-800°C were determined and they show very good agreement. The SEM micrograph is also used to explain the morphology of the powder. © 2004 Elsevier Ltd and Techna Group S.r.l. All rights reserved.